Effects of different arterial occlusion pressures during blood flow restriction exercise on muscle damage: a single-blind randomized controlled trial - Kevin Happ; Sarah Barawi; Daniel Niederer; Carsten Schwiete; Christine Heinrich; Alexander Franz; Patrick Wahl; Michael Behringer (Scientific Reports)
Abstract Blood flow restriction (BFR) training has been shown to induce exercise-induced muscle damage (EIMD) in some cases, although findings are inconsistent and the influence of the applied arterial occlusion pressure (AOP) remains unclear. This single-blind, randomized controlled trial investigated the effects of different percentages of AOP on EIMD and acute physiological responses in 40 participants allocated to four groups: no pressure (NP), low pressure (LP; 50% AOP), medium pressure (MP; 75% AOP), and high pressure (HP; 100% AOP). Participants performed unilateral knee extensions at 30% of their one-repetition maximum up to four sets of 20 repetitions or until failure. EIMD was primarily assessed by the changes in isokinetic peak torque 24 h, 48 h and 72 h post-exercise (Δ to baseline). Secondary markers included perceived pain, blood biomarkers (creatine kinase, myoglobin) and muscle swelling. Additionally, acute physiological responses were assessed, including continuous measurement of muscle oxygen saturation (SmO2) during exercise, perceived exertion (RPE) immediately after the exercise bout, and blood lactate concentration measured at 1, 3, 7, and 10 min post-exercise. NP showed greater strength loss at 24 h post-exercise compared to MP (MD = − 9.95, p = .042, 95% CI [− 19.7, − 0.19]) and HP (MD = − 10.51, p = .034, 95% CI [− 20.52, − 0.49]). Pain ratings were higher in NP compared to MP (p = .001) and HP (p = .003) at 24 h post, and remained elevated at 48 h compared to MP (p = .003) and HP (p = .047). NP and LP completed more repetitions than MP and HP. HP exhibited a greater reduction in SmO2compared to NP. Perceived exertion was higher in MP and HP. LP showed higher average lactate concentrations than NP (p = .020). CK and MB responses showed no time-specific group differences. These findings suggest that BFR training, even at higher pressures, does not increase EIMD compared to free-flow exercise, and that MP and HP may even attenuate strength loss and pain following exercise.